Aboriginal Graduate Student and a Non-Aboriginal Faculty Supervisor: A Relationship Examined - Lee, Danica; Poulsen, John (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2016)
This article investigates and shares the elements of a successful working relationship between an Aboriginal graduate student and a non-Aboriginal faculty supervisor. In order to explore the emerging relationship, each author reflected on the experience by recording weekly journal entries and examining supporting literature. Through examination of the literature and their own metacognition, the authors came to the realization that theirs’ was a productive and enjoyable relationship due in large part to mutual respect and consistent back and forth feedback.